2019
DOI: 10.1371/journal.pgen.1008404
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryote hybrid genomes

Abstract: Interspecific hybridization is the process where closely related species mate and produce offspring with admixed genomes. The genomic revolution has shown that hybridization is common, and that it may represent an important source of novel variation. Although most interspecific hybrids are sterile or less fit than their parents, some may survive and reproduce, enabling the transfer of adaptive variants across the species boundary, and even result in the formation of novel evolutionary lineages. There are two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 165 publications
(225 reference statements)
1
86
0
Order By: Relevance
“…By contrast, in interspecific hybrids, we observed centromere stretching in 70% of spermatocytes. In most cases the length was >3 µm ( Figure 3 I,J, Table S1 [ 6 ]), and in some nuclei it reached ≥10 µm (for example, Figure 3 K). In interspecific hybrids, the centromeric region of the metacentrics was strongly stretched ( Figure 3 H,K and Figure S4 B,F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in interspecific hybrids, we observed centromere stretching in 70% of spermatocytes. In most cases the length was >3 µm ( Figure 3 I,J, Table S1 [ 6 ]), and in some nuclei it reached ≥10 µm (for example, Figure 3 K). In interspecific hybrids, the centromeric region of the metacentrics was strongly stretched ( Figure 3 H,K and Figure S4 B,F).…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid sterility may develop between species or genetically differentiated populations, as a primary or secondary feature of reproductive isolation [ 1 , 2 , 3 , 4 , 5 ]. Two genetic materials in a heterozygous admixed genome interact in various compositions [ 6 ] and these hybrid states are often referred to as “genomic conflict” [ 7 , 8 ], “genomic shock” [ 9 , 10 ], “genomic stress” [ 9 , 11 ], or “nucleus at war” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…52 ) and is a compliment to speciation genomics studies characterizing the genomic basis of this process (e.g. 17,111 ). Herein we have shown that hybridization may act as a generative force across a phylogenetic order, and additional studies at such macroevolutionary scales are needed to determine if this pattern holds more generally across the tree of life.…”
Section: Narrowmentioning
confidence: 99%
“…Hybridization has also been associated with the production of maladapted individuals, leading to evolutionary dead-ends (Barton, 2001). However, more recent studies suggest this process can also have beneficial outcomes, as advantageous traits can be shared between multiple groups (Pardo-Diaz et al, 2012;Runemark, Vallejo-Marin, & Meier, 2019), hybrids have higher fitness than their parental lineages (i.e., hybrid vigor; Chen, 2013), and hybridization can also lead to the formation of new species and generate adaptive radiations (Meier, Marques, Wagner, Excoffier, & Seehausen, 2018;Meier et al, 2019;Seehausen, 2004).…”
Section: Introductionmentioning
confidence: 99%